1992
DOI: 10.1152/jn.1992.68.4.1012
|View full text |Cite
|
Sign up to set email alerts
|

Responses of single facial taste fibers in the channel catfish, Ictalurus punctatus, to amino acids

Abstract: SUMMARYAND CONCLUSIONS 1. Amino acids and nucleotides stimulate taste receptors of teleosts. In this report, responses to these compounds of 105 facial taste fibers (79 fully characterized) that innervate maxillary barbel taste buds of the channel catfish (Ictalurus punctatus) were analyzed.2. The fully characterized facial taste fibers that responded to amino acids ( y2 = 68) were generally poorly responsive to nucleotides and related substances (NRS), whereas the fibers responsive to NRS (~2 = 11) were poorl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 52 publications
6
43
0
Order By: Relevance
“…TCA was a relatively poor stimulus compared both with TCDC and with the two additional bile salts tested, CDC and GCDC, that are not produced by channel catfish. The data indicate that thresholds to bile salts are lower than those for amino acids in the facial taste system in the same species (Kohbara et al, 1992) and are 1-2 log units higher than those recorded for TCA in the rainbow trout (Yamashita et al, 2006). Although the thresholds to bile salts were lower than those to amino acids in the facial taste system, amino acids elicited greater integrated response magnitudes at equivalent stimulus concentrations.…”
Section: Dose-response Propertiesmentioning
confidence: 66%
See 2 more Smart Citations
“…TCA was a relatively poor stimulus compared both with TCDC and with the two additional bile salts tested, CDC and GCDC, that are not produced by channel catfish. The data indicate that thresholds to bile salts are lower than those for amino acids in the facial taste system in the same species (Kohbara et al, 1992) and are 1-2 log units higher than those recorded for TCA in the rainbow trout (Yamashita et al, 2006). Although the thresholds to bile salts were lower than those to amino acids in the facial taste system, amino acids elicited greater integrated response magnitudes at equivalent stimulus concentrations.…”
Section: Dose-response Propertiesmentioning
confidence: 66%
“…effectiveness of bile salts relative to that for amino acids -the more well-established tastants for channel catfish (Caprio, 1978;Kohbara et al, 1992). Only prominent phasic responses were evident for both classes of stimuli (Fig.…”
Section: Characteristics Of the Integrated Taste Responses To Bile Saltsmentioning
confidence: 94%
See 1 more Smart Citation
“…Nevertheless, 5 0 -nucleotides are well known and powerful gustatory stimulants on their own (Hara, 1994;Kubitza et al, 1997;Li and Gatlin, 2006). For instance, facial taste fibers in channel catfish that respond to AAs have a low responsiveness to nucleotides and vice versa (Kohbara et al, 1992).…”
Section: Taste Preferencesmentioning
confidence: 99%
“…Also, peptides tested so far are less effective than their AA residues (Kasumyan and Døving, 2003). Furthermore, the existence of different independent receptor mechanisms (not necessarily stimulatory) has been proposed for L-Ala, L-Arg, and L-Pro, based on electrophysiological studies in channel catfish (Kanwal and Caprio, 1983;Kohbara et al, 1992;Kumazawa et al, 1998), and it was additionally suggested that L-Ala and other short-chain neutral AA activate GPCRs that indirectly gate membrane ion channels via second messengers while L-Arg and L-Pro directly activate cation ion channels (Kohbara et al, 1992;Kumazawa et al, 1998). The induction of ion channel activity by L-Arg (and its blocking by D-Arg) binding to ligand-gated ion channel receptors from catfish barbel epithelium was later clearly demonstrated by Grosvenor et al (2004).…”
Section: Taste Preferencesmentioning
confidence: 99%